Abnormal B cell glycosylation in autoimmunity: A new potential treatment strategy - Morel, Marie; Pochard, Pierre; Echchih, Wiam; Dueymes, Maryvonne; Bagacean, Cristina; Jousse-Joulin, Sandrine; Devauchelle-Pensec, Valérie; Cornec, Divi; Jamin, Christophe; Pers, Jacques-Olivier; Bordron, Anne (Frontiers in Immunology, 2022)
Systemic lupus erythematosus (SLE) and primary Sjögren’s syndrome (pSS) are two autoimmune diseases characterized by the production of pathogenic autoreactive antibodies. Their etiology is poorly understood. Nevertheless, some elements are pointed out including infections, epigenetic mechanisms, etc. Among them, glycosylation is a physiological process likely involved. Abnormal glycosylation is seen on SLE T cell markers as well as on autoantibodies in pSS. Such dysregulation suggest that a defective glycosylation could also occur in B cells modifying their behavior and their reactivity. The aim of this study was to investigate B cell subset glycosylation in SLE, pSS and healthy donors, and to extend the glycan profile to serum proteins and immunoglobulins. Using optimized lectin-based tests, we demonstrated particular glycosylation profiles on B cell subsets specifically altered in both diseases. Compared to healthy donors, hypofucosylation was observed on SLE B cells while hyposialylation was present on pSS B cells only. Along with these features, SLE B lymphocytes are carrying more Gal-GlcNAc/Gal-GalNAc residues on their cell surface markers. Interestingly, some similar alterations were observed in serum proteins including immunoglobulins. These findings point out that any perturbation of natural glycosylation processes in B cells could lead to the development of pathogenic autoantibodies. Correlation between the extent of these alterations and the severity of the autoimmune diseases could establish the B cell glycoprofile as a biomarker of choice to characterize pathologies and the used of adapted therapeutics for the patients.